Circulating tumour cells as a potential screening tool for lung cancer (the AIR study): protocol of a prospective multicentre cohort study in France. Issue 12 (26th December 2017) - Leroy, Sylvie; Benzaquen, Jonathan; Mazzetta, Andrea; Marchand-Adam, Sylvain; Padovani, Bernard; Israel-Biet, Dominique; Pison, Christophe; Chanez, Pascal; Cadranel, Jacques; Mazières, Julien; Jounieaux, Vincent; Cohen, Charlotte; et al.
Abstract : Introduction: Lung cancer (LC) is the leading cause of death from cancer. Early diagnosis of LC is of paramount importance in terms of prognosis. The health authorities of most countries do not accept screening programmes based on low-dose chest CT (LDCT), especially in Europe, because they are flawed by a high rate of false-positive results, leading to a large number of invasive diagnostic procedures. These authorities advocated further research, including companion biological tests that could enhance the effectiveness of LC screening. The present project aims to validate early diagnosis of LC by detection and characterisation of circulating tumour cells (CTCs) in a peripheral blood sample taken from a prospective cohort of persons at high-risk of LC. Methods and analysis: The AIR Project is a prospective, multicentre, double-blinded, cohort study conducted by a consortium of 21 French university centres. The primary objective is to determine the operational values of CTCs for the early detection of LC in a cohort of asymptomatic participants at high risk for LC, that is, smokers and ex-smokers (≥30 pack-years, quitted ≤15 years), aged ≥55 years, with chronic obstructive pulmonary disease (COPD). The study participants will undergo yearly screening rounds for 3 years plus a 1-year follow-up. Each round will include LDCT plus peripheral blood sampling for CTC detection. Assuming 5% prevalence of LC in the studied population and a 10% dropout rate, a total of at least 600 volunteers will be enrolled. Ethics and dissemination: The study sponsor is the University Hospital of Nice. The study was approved for France by the ethical committee CPP Sud-Méditerranée V and the ANSM (Ministry of Health) in July 2015. The findings of the trial will be disseminated through peer-reviewed journals and national and international conference presentations. Trial registration number: NCT02500693 .